Nanotechnologies in medicine and pharmacy - Геращенко, І.І.; Васильченко, О.А. (Problems of Environmental Biotechnology, 2012)
In this article the basic directions of nanoteсhnologies development in modern experimental and practical medicine and pharmaceutics on the example of foreign and domestic achievements are reviewed.